Association of early vertebroplasty with risk of hip replacement: A nationwide population-based cohort study in Taiwan. Issue 27 (2nd July 2020) - Li, Chiao-Zhu; Li, Chiao-Ching; Tang, Chi-Tun; Chung, Chi-Hsiang; Ou, Chien-Yu; Chen, Chun-Lin; Chen, Nan-Fu; Chung, Tzu-Tsao; Hueng, Dueng-Yuan; Ma, Hsin-I; Liu, Ming-Ying; Chen, Yuan-Hao; et al.
Abstract : Abstract: Studies show that vertebral fractures could predict the risk of hip fractures. We aimed to evaluate the potential benefits of whether the timing of vertebroplasty (VP) for vertebral fracture associated with the risk of hip fracture for hip replacement. We identified 142, 782 patients from the Taiwan National Health Insurance Database with thoracolumbar vertebral fracture (International Classification of Diseases, Ninth Revision, Clinical Modification:805.2–805.9) who were followed up from 2000 to 2013. These patients were divided into those who underwent VP (VP group) (International Classification of Diseases, Ninth Revision, Clinical Modification : 78.49) within 3 months and those who did not (non-VP group). After adjusting for the confounding factors, the Cox proportional hazards analysis was used to estimate the effect of early VP on reducing the risk of hip fracture. The difference in the risk of hip replacement, between the VP group and non-VP group was estimated using the Kaplan-Meier method with the log-rank test. In the 14-year follow-up, the cumulative incidence rate of hip replacement in the VP group was lower than that in the non-VP group (0.362% and 0.533%, respectively, long-rank P < .001). There was a significant difference between the 2 groups since the first-year follow-up. Our study showed that early VP performed to avoid progression of the kyphotic changes following thoracolumbar vertebral fracture may reduce the risk of hip fracture. These results, obtained from retrospective data, indicate that a prospective study is warranted.